Faktor Keterbatasan Polisi Dalam Melakukan Penyidikan Tindak Pidana Penyebaran Berita Bohong Di Media Oline - Dandi Alwanda (JOURNAL of LEGAL RESEARCH, 2022)
Law No. 2 of 2002 concerning the Indonesian State Police which contains all regulations and understandings regarding the police, and the procedures of a police officer carrying out their duties. Hoax news or hoaxes are news that is manipulated, reduced or added to obscuring the true meaning of a particular information and news, lately fake news often spreads and increasingly unsettling the public because it is difficult to identify the news. This research is normative juridical research with a case approach. The results of research and discussion show that the limitations of the police in investigating the crime of spreading false news in online media are the legal factor itself is the regulation of invitations that have not been applied effectively, then the factor of inadequate facilities or facilities, community factors that tend to be dependent on social media. While the police's efforts in countering the criminal act of spreading fake news consist of three points, namely pre-emtive, preventive, repressive.